No-queue road pricing: A comprehensive policy instrument for Europe?. (October 2022) - Schubert, Daniel; Sys, Christa; Vanelslander, Thierry; Roumboutsos, Athena
Abstract: European roads have become increasingly congested over the last decades. Addressing congestion is a multi-faceted issue. In the short term, adequate incentives may shift peak car travel to other times, roads or modes. In the longer term, investment projects should be prioritized to provide an efficient supply of road capacity. This also touches upon funding issues. This paper eclectically reviews the literature to demonstrate the potential of no-queue road pricing (NQRP, i.e., setting tolls responsive to real-time traffic conditions) to contribute to a European policy framework and address three challenges: (i) congestion management; (ii) investment project prioritization; and (iii) sustainable road funding. The limitations of NQRP and reasons why it has not been implemented anywhere in Europe yet are examined. Potential implementation issues are discussed, and a conceptual framework for socially acceptable NQRP is drafted. Graphical abstract: Image 1 Highlights: Roads suffer from congestion, inefficient project prioritization and funding gaps. In theory, no-queue road pricing (NQRP) offers a solution, but is not used in Europe. To contribute to a EU policy framework, NQRP needs to gain public acceptance. This research presents five concrete suggestions for socially acceptable NQRP design. These comprise local specifics, incentives, alternatives, habituation and transparency.